Dissecting the Cell Entry Pathway of Baculovirus by Single-Particle Tracking and Quantitative Electron Microscopic Analysis - Qin, Fujun (J Virol, 2019)
The budded virus of Autographa californica multiple nucleopolyhedrovirus (AcMNPV) infects insect cells through mainly clathrin-mediated endocytosis. However, the cell entry pathway of AcMNPV remains unclear. In this study, by using population-based analysis of single-virus tracking and electron microscopy, we investigated the internalization, fusion behavior, and endocytic trafficking of AcMNPV. AcMNPV internalization into host insect cells was facilitated by actin polymerization and dynamin. After incorporation into early endosomes, the AcMNPV envelope fused with the membranes of early endosome, allowing for nucleocapsid release into the cytoplasm. Microtubules were implicated in the bidirectional and long-range transport of virus-containing endosomes. In addition, microtubule depolymerization reduced the motility of virus-bearing early endosomes, impairing the progression of infection beyond enlarged early endosomes. These findings demonstrated that AcMNPV internalization was facilitated by actin polymerization in a dynamin-dependent manner, and nucleocapsid release occurred in early endosomes in a microtubule-dependent manner. This study provides mechanistic and kinetic insights into AcMNPV infection and enhance our understanding of the infection pathway of baculoviruses. IMPORTANCE Baculoviruses are used widely as environmentally benign pesticides, protein expression systems, and potential mammalian gene delivery vectors. Despite the significant application value, little is known about the cell entry and endocytic trafficking pathways of baculoviruses. In this study, we demonstrated that the alphabaculovirus AcMNPV exhibited actin- and microtubule-dependent transport for nucleocapsid release predominantly from within early endosomes. In contrast to AcMNPV transduction in mammalian cells, its infection in host insect cells is facilitated by actin polymerization for internalization and microtubules for endocytic trafficking within early endosomes, implying that AcMNPV exhibits cell type specificity in the requirement of the cytoskeleton network. In addition, experimental depolymerization of microtubules impaired the progression of infection beyond enlarged early endosomes. This is the first study that dissects the cell entry pathway of baculoviruses in host cells at the single-particle level, which advances our understanding of the early steps of baculovirus entry.